HERD IMMUNITY (KEKEBALAN KELOMPOK) DALAM PEMBERIAN IMUNISASI VAKSIN COVID-19 DI WILAYAH KERJA PUSKESMAS GUGUK PANJANG KELURAHAN AUR KUNING BUKITTINGGI - Mera Delima; Andrye Fernandes; Yendrizal Jafri; Yessi Andriani; Rinawati Kasrin (Universitas Pahlawan Tuanku Tambusai, 2022)
In Indonesia, the target of herd immunity/(herd immunity) is 70% in accordance with the characteristics of the spread of Covid-19. The development and discovery of the Covid-19 vaccine as well as minimal public compliance raises the issue of